2009
DOI: 10.1086/648090
|View full text |Cite
|
Sign up to set email alerts
|

Response to Vicriviroc in Treatment‐Experienced Subjects, as Determined by an Enhanced‐Sensitivity Coreceptor Tropism Assay: Reanalysis of AIDS Clinical Trials Group A5211

Abstract: The enhanced sensitivity Trofile assay was used to re-test co-receptor usage at study screening and entry for the 118 ACTG A5211 treatment-experienced subjects who had CCR5-tropic (R5) virus by the original Trofile assay at study screening. Among 90 vicriviroc recipients, a significantly (P<0.001) greater mean reduction in HIV-1 RNA was observed in 72 subjects with R5 virus versus 15 subjects reclassified with dual/mixed-tropic viruses at screening: −1.11 vs. −0.09 (day 14), −1.91 vs. −0.57 (week 24) log10 cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 8 publications
2
53
0
2
Order By: Relevance
“…As a consequence, assay sensitivity (i.e., percentage of the non-R5 minority variants that can be detected consistently) has played a major role on the success of clinical trials of CCR5 antagonists (13,58,59,61,62). Here, we have consistently shown that VERITROP has a 0.3% sensitivity threshold for detecting CXCR4-using minor variants, which is similar to the sensitivity reported for the widely used ESTA (42).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…As a consequence, assay sensitivity (i.e., percentage of the non-R5 minority variants that can be detected consistently) has played a major role on the success of clinical trials of CCR5 antagonists (13,58,59,61,62). Here, we have consistently shown that VERITROP has a 0.3% sensitivity threshold for detecting CXCR4-using minor variants, which is similar to the sensitivity reported for the widely used ESTA (42).…”
Section: Discussionsupporting
confidence: 81%
“…The use of CCR5 antagonists in antiretroviral regimens has relied on the ability of HIV-1 tropism assays to detect viruses capable of using CXCR4 to enter the host cell (29,(58)(59)(60). As a consequence, assay sensitivity (i.e., percentage of the non-R5 minority variants that can be detected consistently) has played a major role on the success of clinical trials of CCR5 antagonists (13,58,59,61,62).…”
Section: Discussionmentioning
confidence: 99%
“…Cell-based assays for entry phenotype test either virus isolates or viruses pseudotyped by using cloned viral env genes. Phenotyping consists of infecting cells expressing CD4 and either CCR5 or CXCR4 (5,6) or inhibiting infection with antagonists of CCR5 and/or CXCR4. Alternatively, assignment of coreceptor tropism by sequence analysis has been based on sequencing of the V3 loop coding domain of the viral env gene.…”
mentioning
confidence: 99%
“…15 A more recent publication demonstrated that a newly enhanced tropism assay would be a better screening tool for eligibility of the antagonist by identifying genetic variants below the detection limit of the original assay. 16 This example demonstrates the moving target of accuracy in this rapidly evolving field.…”
Section: Diagnostic and Drug Researchmentioning
confidence: 90%